Conventional Domestic Waste Treatment Eco-friendly Composting technology: a Review - Riska Riska; Fanni Febrianty Waode; Mirna Wati; Nur Cahyani Dwi Lestari (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2026)
Background: Waste management remains a major environmental challenge worldwide, particularly in developing countries such as Indonesia. Waste is generated from both human activities and natural processes, and improper handling can lead to soil, water, and air pollution. Therefore, effective household waste management is essential to maintain environmental cleanliness and sustainability. Composting is one of the most environmentally friendly methods for managing organic household waste. Objective: This study aimed to improve community knowledge regarding proper and environmentally friendly organic waste management practices through composting. Methods: This study employed a community-based educational approach on organic waste management through composting. Educational activities were conducted to increase participants’ understanding of waste sorting and environmentally friendly waste treatment methods. The effectiveness of the program was assessed descriptively based on participants’ knowledge and awareness of organic waste management practices. Results: The findings indicated that waste management remains a critical issue requiring special attention, particularly in developing countries. Participants demonstrated increased awareness of the importance of proper waste management and the role of composting in reducing household organic waste. Effective waste segregation was recognized as a key factor in achieving efficient and environmentally sustainable waste management. The educational intervention also enhanced participants’ understanding of composting as a practical method for converting organic waste into useful products while reducing environmental pollution. Conclusion: Composting is an effective and environmentally friendly approach to managing household organic waste. Increasing public knowledge and awareness regarding waste segregation and composting practices can contribute to improved environmental sustainability and support community-based waste management efforts. Keywords: Waste Management; Household Waste; Organic Waste; Composting; Environmental Sustainability; Waste Segregation